DEPRESSION IN A GROUP OF PENSIONERS BELONGING TO PHYSICAL ACTIVITY AND /OR ASSOCIATIONS PROGRAMS, UNIVERSIDAD DE ANTIOQUIA, MEDELLÍN 2005 - Patiño V., Fredy Alonso; Cardona Arango, Doris (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Objective: To assess the frequency of depression in a group of pensioners belonging to physical activity and/or associations of Universidad de Antioquia. Materials and Methods: A cross descriptive study was carried between April and May 2005. One hundred pensioners taking part in physical activity and/or associations were selected: Fifty men and ﬁfty women. Median age: 65.7 years. The Yesavage Geriatric Depression Scale was applied and some demographic, economic, functional, affective, familiar and time use aspects were surveyed. Results: Six per cent total depression was found. Highest values were found in women, in people more recently retired, in people without labor activities after retirement, in people considering they suffer bad economic situation and in persons who do not performed physical activities. A statistically signiﬁcant was found especially between depression and the feeling of bad economic situation. Conclusions: Depression was inferior compared with other researches. That could be explained by the sample and possibly for the protective factor implicit in group sharing.